(untitled) (Journal of Academic Research, 2026)
This study aimed to investigate the impact of psychological empowerment, across its four dimensions (Meaning, Competence, Self-determination, and Impact), on enhancing Organizational Citizenship Behavior (OCB) among employees at Misrata Medical Center. The study adopted a descriptive-analytical approach, and data were collected using a questionnaire distributed to a random sample of (62) employees from the hospital’s administrative and technical staff. The data were analyzed using the Statistical Package for the Social Sciences (SPSS), employing descriptive statistics, correlation analysis, and linear regression to test the hypotheses. The study reached several key findings: there is a high level of psychological empowerment among employees, with "Self-determination" ranking first, followed by "Competence" and "Meaning." The results also revealed a positive and statistically significant correlation between psychological empowerment in all its dimensions and organizational citizenship behavior. Hypothesis testing further confirmed that psychological empowerment explains a significant portion of the variance in citizenship behaviors, affirming that enhancing the sense of empowerment effectively encourages employees to engage in voluntary actions that exceed their formal job requirements, ultimately serving the hospital’s interests. Based on these findings, the study recommended that the hospital management should continue to grant employees more authority and autonomy in decision-making related to their tasks to further enhance their loyalty and positive performance.